Dynamics of CO2 Concentration and Meteorological Parameters at the Starzach Mofette Site in 2020 Observed with Sensirion SCD30 Sensor and Gill MaxiMet GMX541 Compact Weather Station - Yann Büchau; Jens Bange (PANGAEA, 2023)
This dataset comprises measurements of a Gill MaxiMet GMX541 compact weather station in 2 m height above ground and a Sensirion SCD30 low-cost CO2 sensor 50cm above a dry mofette at the Starzach site from January to October 2020. Diurnal dynamics of meteorological parameters (temperature, wind speed, incoming solar radiation) are expectedly prominent. The wind direction shows a strong diurnal cycle, especially in summer due to the valley orography at the site. CO2 concentrations are generally elevated and increase up to 40000 ppm (sensor output limit) during the night due to accumulation caused by low wind speeds and reduced mixing.